Blebbistatin as a novel antiviral agent targeting equid herpesvirus type 8 - Li, Liangliang; Cui, Xiu; Yu, Yue; Sun, Qi; Li, Wenjing; Li, Yubao; Li, Shuwen; Chen, Li; Khan, Muhammad Zahoor; Wang, Changfa; Wang, Tongtong (Frontiers in Veterinary Science, 2024)
Equid herpesvirus type 8 (EqHV-8) poses a significant threat to equine health, leading to miscarriages and respiratory diseases in horses and donkeys, and results in substantial economic losses in the donkey industry. Currently, there are no effective drugs or vaccines available for EqHV-8 infection control. In this study, we investigated the in vitro and in vivo antiviral efficacy of Blebbistatin, a myosin II ATPase inhibitor, against EqHV-8. Our results demonstrated that Blebbistatin significantly inhibited EqHV-8 infection in Rabbit kidney (RK-13) and Madin-Darby Bovine Kidney (MDBK) cells in a concentration-dependent manner. Notably, Blebbistatin was found to disrupt EqHV-8 infection at the entry stage by modulating myosin II ATPase activity. Moreover, in vivo experiments revealed that Blebbistatin effectively reduced EqHV-8 replication and mitigated lung pathology in a mouse model.Collectively, these findings suggest that Blebbistatin holds considerable potential as an antiviral agent for the control of EqHV-8 infection, presenting a novel approach to addressing this veterinary challenge.